Leitura, escuta e produção oral de contos de terror na formação do leitor literário - Montenegro, Eveline de Sousa (2024)
This propositional research aims to develop the reading and listening skills of 9th-grade students through horror stories, with the goal of nurturing the development of literary readers capable of enhancing their reading and oral communication abilities. Considering the intersection between reading, listening, orality, and reader development, the proposed methodological approach is the reading circle, developed based on the proposals of Cosson (2018, 2019, 2021) and the systematization presented by MAIS PAIC (Ceará, 2015). The reading circles consist of a didactic notebook organized into modules; internally, the circles are divided into stages of motivation, reading, conversation, and register of horror stories, enabling the integrated development of language practices in both oral and written forms to foster and expand literary reader development. Theoretical support for the design, implementation, and analysis of Reading Circles, as a tool for literary literacy, is drawn from Kleiman (1989, 2012), Soares (1998), Daniels (2002), Petit (2009, 2010), Bajour (2012), and Cosson (2018, 2019, 2021). Regarding the importance of systematizing oral instruction as part of the circles and as school content, reference is made to Schneuwly (2002), Dolz, Noverraz, and Schneuwly (2004), Marcuschi (2010), Carvalho and Ferrarezi Jr. (2018). Concerning the horror story genre, theoretical foundations are drawn from Todorov (2004), Gotlib (2006), and Vasconcelos (2021). To understand the historical aspects of the genre so that students can engage in literary reading practices, create and/or recreate horror stories through reflection on them, we rely on studies on Discursive Traditions by Kabatek (2006), Longhin (2014), Mendes (2020), Zavam, Dolz, and Gomes (2022). In addition to these authors, our research is supported by educational regulatory documents: National Curriculum Parameters for Portuguese Language (1998), National Common Curricular Base (2018), and Ceará's Curricular Referential Document (2019). The methodology adopted involves the proposition of a didactic notebook based on reading circles, Daniels' functions, and Discursive Traditions. To support the critical analysis of the material, theoretical foundations ranging from literary literacy studies to perspectives on oral instruction were utilized, ensuring its academic and pedagogical robustness. It is hoped that the proposal outlined here will inspire other educators and researchers, encouraging them to explore similar teaching strategies, in order to promote a more enriching and meaningful literary education for students."